Knockdown of PDPN in astrocytes reduces hippocampal inflammation in T2DM mice - Wang, Xiaohang; Wang, Qianqian; Cai, Zhensheng; Ni, Chengming; Wang, Huan; Liu, Hui; Zhao, Yusong; Wang, Jinbang; Liu, Subo; Wang, Xueying (Frontiers in Immunology, 2025)
AimsIndividuals with type 2 diabetes mellitus (T2DM) are at-risk for developing vascular dementia (VaD). Hyperglycemia leads to the activation of astrocytes. These activated cells produce proinflammatory mediators like cytokines or chemokines, that cause cerebrovascular damage. Previous sequencing showed Pdpn’s high expression in activated stellate cells and possible inflammation involvement. Our study aims to reveal its role in T2DM-induced hippocampal inflammation in VaD.MethodsFirstly, we will validate the expression of the Pdpn gene in T2DM astrocytes via qPCR and Western blot. Subsequently GFAP-specific promoter adeno-associated virus(AAV)carrying interfering sequence was used to knockdown the key gene in astrocytes of T2DM mice. Then the step-down test was conducted to assess the cognition level. The fluorescence intensities of IL-1β, IL-6, TNF-α, and TGF-β were measured via immunofluorescence assay to assess the level of inflammation in the brain after the key gene knockdown.ResultsAfter the validation of transcriptome sequencing, the Pdpn gene was identified as a key gene upregulated in astrocytes from T2DM. Comparing to T2DM mice, knocking down Pdpn in astrocytes extended the latency and decreased the number of errors in T2DM mice, showing improved memory impairment. After the cognition assessment, the mice were euthanized, and the inflammatory factors associated to the VaD were detected by immunofluorescence. We showed that the fluorescence intensities of IL-1β, IL-6, TNF-α, and TGF-β1 in hippocampus were decreased after the Pdpn knocking down in astrocytes of T2DM mice.ConclusionIn summary, this study demonstrates that Pdpn exerts a novel player in T2DM-induced neuroinflammation and cognitive decline. Knocking down Pdpn in astrocytes shows a protective effect in hippocampal inflammation and VaD.